Hybrid approach to it projects management in telecommunication - Smidovych, L. S.; Kulyk, Y. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of the report is to present hybrid approach to management of IT projects in telecommunications, that combines linear and agile project management methodologies to achieve better outcomes in IT projects. It is proposed to follow a linear (i.e. Waterfall) approach for the planning and design phases of the project, and then transition to an Agile approach for the development and testing phases.
Keywords: information technology; IT project management; iterative; project life cycle